Effects of sacubitril/valsartan in patients with cancer therapy-related heart failure - Marina V. Vitsenya; Alexandra V. Potekhina; Svetlana V. Gavryushina; Nursiiat M. Ibragimova; Olga V. Stukalova; Valery P. Masenko; Tatiana V. Sharf; Fail T. Ageev (Терапевтический архив, 2023)
Aim. To evaluate the effect of Sacubitril/Valsartan (S/V) on the functional status, systolic and diastolic function of the left ventricle (LV), tolerability of therapy and to determine predictors of its effectiveness in patients with cancer therapy-related heart failure (СTRHF).